Increased plasma levels of soluble vascular endothelial growth factor (VEGF) receptor 1 (sFlt-1) in women by moderate exercise and increased plasma levels of VEGF in overweight/obese women - Makey, Kristina L. (2013)
The incidence of breast cancer is increasing worldwide, and this seems to be related to an increase in lifestyle risk factors, including physical inactivity, and overweight/obesity. We previously reported that exercise induced a circulating angiostatic phenotype characterized by increased sFlt-1 and endostatin and decreased unbound-VEGF in men. However, there is no data on women. The present study determines the following: 1) whether moderate exercise increased sFlt-1 and endostatin and decreased unbound-VEGF in the circulation of adult female volunteers; 2) whether overweight/obese women have a higher plasma level of unbound-VEGF than lean women. 72 African American and Caucasian adult women volunteers aged from 18–44 were enrolled into the exercise study. All the participants walked on a treadmill for 30 minutes at a moderate intensity (55–59% heart rate reserve), and oxygen consumption (VO2) was quantified by utilizing a metabolic cart. We had the blood samples before and immediately after exercise from 63 participants. ELISA assays (R&D Systems) showed that plasma levels of sFlt-1 were 67.8±3.7 pg/ml immediately after exercise (30 minutes), significantly higher than basal levels, 54.5±3.3 pg/ml, before exercise (P < 0.01; n=63). There was no significant difference in the % increase of sFlt-1 levels after exercise between African American and Caucasian (P=0.533) or between lean and overweight/obese women (P=0.892). There was no significant difference in plasma levels of unbound VEGF (35.28±5.47 vs. 35.23±4.96 pg/ml; P=0.99) or endostatin (111.12±5.48 vs. 115.45±7.15 ng/ml; P=0.63) before and after exercise. Basal plasma levels of unbound-VEGF in overweight/obese women were 52.26±9.6 pg/ml, significantly higher than basal levels of unbound-VEGF in lean women, 27.34±4.99 pg/ml (P < 0.05). The results support our hypothesis that exercise-induced plasma levels of sFlt-1 could be an important clinical biomarker to explore the mechanisms of exercise training in reducing breast cancer progression and that VEGF is an important biomarker in obesity and obesity-related cancer progression.